Assessment of Heavy Metals in Edible Fruits Sold in Selected Markets in Ihiala Local Government Area, Anambra State - Uchenna, Igwe Peter; Onyebuchi, Ezekwesili Janet (Journal of Sustainability and Environmental Management, 2023)
This study assessed the concentration of heavy metals in edible fruits sold in selected markets in Ihiala Local Government Area, Anambra State. Despite the nutritional benefits obtained from fruit consumption, the presence of heavy metals accompanying it from the environment draws scientific concerns affecting the human health. The multi-stage and random sampling techniques were used in dividing the area into three with three markets. Ninety-five fruit sellers participated in the study. The instruments used for data collection were field observation, questionnaire and laboratory analysis. Twelve fruit samples of banana, watermelon, apple and pineapple, four from three markets were collected. Also, three samples of unripe banana fruits were collected, to compare the percentage increase in the concentration of arsenic that might be arising from the use of calcium carbide. ANOVA was used for data analysis. Results revealed that the concentrations of Zn, Ni, Cu, Pb and Cr in all fruits were within WHO/FAO’s acceptable limits of heavy metals in fruits. Whilst As and Fe were above the limit. Results also indicated an increase in the concentration of As in ripe banana compared with unripe one. Findings showed that 80% of the respondents were not aware of the health implication of consuming of CaC2 ripen fruits. There was no significant relationship between the concentration of Zn, Ni, Cu, Pb and Cr in fruits sold in markets and human health risks as the Fcal value of the metals was less than Fcrit at (P<0.05) level of significance. However, there was a significant relationship between the concentrations of As and Fe and human health risk as Fcal was greater than Fcrit at (P˃0.05) level of significance, which shows the serious human health risk associated with As and Fe toxicity.